DISABILITY IS AN AREA RICH WITH SOCIOLOGICAL OPPORTUNITY - ALBRECHT, GARY L. (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Disability has recently captured the public’s attention in American society, stimulated sociological inquiry, and emerged as an important priority for policy makers. This is due to the increased prevalence of functional limitations in society as a result of an aging population, technological interventions that prolong the lives of persons with disabling chronic illnesses, unhealthy lifestyles and broadened definitions of disability. The salience of the problem is highlighted by the growing visibility of persons with disabilities in public spaces as a result of the Americans with Disabilities Act of 1990 (ADA). Increasingly accessible environments, the construction of disability as a social problem, personal experiences with family members, coworkers and friends who experience the impact of disability on their lives and the public activism of the disability community all contribute to a public awareness of disability.